Advanced Microparticulate/Nanoparticulate Respirable Dry Powders of a Selective RhoA/Rho Kinase (Rock) Inhibitor for Targeted Pulmonary Inhalation Aerosol Delivery - Priya Muralidharan; Don Hayes; Jeffrey R. Fineman; Stephen M. Black; Heidi M. Mansour (MDPI AG, 2021)
Pulmonary hypertension (PH) is a progressive disease that eventually leads to heart failure and potentially death for some patients. There are many unique advantages to treating pulmonary diseases directly and non-invasively by inhalation aerosols and dry powder inhalers (DPIs) possess additional unique advantages. There continues to be significant unmet medical needs in the effective treatment of PH that target the underlying mechanisms. To date, there is no FDA-approved DPI indicated for the treatment of PH. Fasudil is a novel RhoA/Rho kinase (ROCK) inhibitor that has shown great potential in effectively treating pulmonary hypertension. This systematic study is the first to report on the design and development of DPI formulations comprised of respirable nanoparticles/microparticles using particle engineering design by advanced spray drying. In addition, comprehensive physicochemical characterization, in vitro aerosol aerosol dispersion performance with different types of human DPI devices, in vitro cell-drug dose response cell viability of different human respiratory cells from distinct lung regions, and in vitro transepithelial electrical resistance (TEER) as air-interface culture (AIC) demonstrated that these innovative DPI fasudil formulations are safe on human lung cells and have high aerosol dispersion performance properties.